Pioneering disadvantage : consumer reactions to marketing mix strategies / M. Sadiq Sohail and Mohamad Farid Mahmood - Sohail, M. Sadiq; Mahmood, Mohamad Farid (Faculty of Business and Management ; UiTM Press, 2000)
Prior research has focused on the early entrant advantage, although a growing body of knowledgde suggests suggests that late movers have been outselling pioneers. In this research, the authors examine the issue of a pay phone service provider in Malaysia. In 1990, the company launches its product and creates an industry, but by the turn of the century, it has a meager 17 per cent of the market share. The Paper examines the specific issue of how a market pioneer has been eclipsed. It is hypothesized that the main cause of the declining sales is the in appropriate marketing mix strategies. The major findings based on a survey include consumers' acceptance level of the product, price, place, promotion, people, process and physical evidence strategies of the company.